2009
DOI: 10.1002/pon.1661
|View full text |Cite
|
Sign up to set email alerts
|

Depression and sexual adjustment following breast cancer in low‐income Hispanic and non‐Hispanic White women

Abstract: Objective-Hispanics are the largest and fastest growing ethnic minority group in the United States and breast cancer is the most commonly diagnosed cancer in Hispanic women. However, Hispanics are underrepresented in the psychosocial breast cancer literature.Methods-This study included 677 low-income women (425 Hispanic, 252 non-Hispanic White) enrolled in the Medi-Cal Breast and Cervical Cancer Treatment Program. Data were gathered through phone interviews conducted in English or Spanish 6 and 18 months follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
49
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 35 publications
7
49
1
1
Order By: Relevance
“…It also is possible that the most distressed women are more likely to decline participation in research, leading to underestimates of prevalence of distress and life disruption. Furthermore, there is evidence that groups with particular characteristics, such as low-income and Latina women (e.g., Christie et al 2010 ;Yanez et al 2011 ), experience relatively high distress and low quality of life. Next, we address specifi c domains of adjustment, with a focus on depression and anxiety, as well as the factors that confer risk for or protection from negative outcomes.…”
Section: The Nature Of Psychological Adjustment In Breast Cancer Survmentioning
confidence: 98%
“…It also is possible that the most distressed women are more likely to decline participation in research, leading to underestimates of prevalence of distress and life disruption. Furthermore, there is evidence that groups with particular characteristics, such as low-income and Latina women (e.g., Christie et al 2010 ;Yanez et al 2011 ), experience relatively high distress and low quality of life. Next, we address specifi c domains of adjustment, with a focus on depression and anxiety, as well as the factors that confer risk for or protection from negative outcomes.…”
Section: The Nature Of Psychological Adjustment In Breast Cancer Survmentioning
confidence: 98%
“…Overall, evidence indicates that women across ethnicities report similar self-image concerns related to their breast cancer treatment [36][37][38] . However, studies also reveal some distinct variations, with Hispanic/ Latina women more likely than non-Hispanic/Latina women to report difficulties one year post-treatment with sexual desire, relaxing and enjoying sex, and becoming sexually aroused and having orgasms 36 .…”
Section: Cultural Factorsmentioning
confidence: 99%
“…However, studies also reveal some distinct variations, with Hispanic/ Latina women more likely than non-Hispanic/Latina women to report difficulties one year post-treatment with sexual desire, relaxing and enjoying sex, and becoming sexually aroused and having orgasms 36 . There are traditional and spiritual values present in the Hispanic/Latino culture around gender roles and sexuality that may be influencing these differences.…”
Section: Cultural Factorsmentioning
confidence: 99%
“…Studies among Hispanic populations suggest that family support is an important stress alleviator in women with breast cancer especially among Latinas with low income (210,216). In addition marital status is an important predictor for psycho-social stress in Latinas with breast cancer (216).…”
Section: Factors Associated With Emotional Hrqolmentioning
confidence: 99%
“…In addition marital status is an important predictor for psycho-social stress in Latinas with breast cancer (216). A comparison between women newly diagnosed with breast cancer and those who had recurrence of the disease showed that being married was associated with better emotional well-being among women in both groups (221).…”
Section: Factors Associated With Emotional Hrqolmentioning
confidence: 99%